La novela urbana amazónica y los cambios en la representación de los Espacios y sujetos de la Amazonía (2019)
This research work is framed in the field of literary history. Therefore, inquire about the origin of the urban novel in the Amazon and how its appearance in the Amazonian literary field modifies, continues or reworked the representations of the spaces and Amazonian subjects present in novels that preceded it. To this end, a collection of works was carried out as widely as possible to determine the said origin and to know who the authors are, their origin, their interests and the place of publication of the works. Derived from the compilation, periodization of the novel about the Amazon was established showing trends and themes by periods, to finally locate the emergence of the Amazon urban novel. The common idea about the marginality of urban Amazon literature is diluted by showing the literary groups created in the region and their intentions to take the representation of the Amazon on their own.